The Association of Bovine Growth Hormone Gene Polymorphism with Milk Performance Traits in Slovak Spotted Cows - Nina Moravčíková; Anna Trakovická; Eva Hazuchová (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this work was to study polymorphism of the bovine growth hormone gene, which is a part of the multiple gene family that contains prolactin and placental lactogen. Genetic variations of this polymorphism have potential effect as genetic markers and could help in the genetic improvement of cattle population. A total of 80 cows of Slovak Spotted breed were genotyped for the bovine growth hormone AluI polymorphism in exon 5 on chromosome 19 by using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and associated with milk production parameters. The genotype and allele frequencies for observed population were determinated and tested to be in Hardy-Weinberg equilibrium. Frequencies of allele L and V were 0.694 and 0.306, respectively. The most frequent was the heterozygous genotype LV. Results from the statistical analysis between AluI polymorphism and milk production parameters – milk, protein and fat yield (kg) were no significant.